Listening by ‘Staying With’ the Absent Child - Alex Orrmalm; Johanna Annerbäck; Anna Sparrman (Barn, 2022)
This article explores what it means to listen to children by moving beyond the notion of voice and staying with the absences of children. In this way, we include the possibly lost, forgotten or unapproachable children in child and childhood research. Our methodological starting point is to listen by ‘staying with’ the absences of children’s verbal voices and physical bodies in two photographs. These photographs depict material artefacts connected to children in vulnerable situations: shrouds for wrapping stillborn babies’ bodies, and children’s shoes as an emblem of children living in hiding from domestic violence. The idea is to explore how we can listen to children whose verbal or embodied encounters we cannot or do not wish to display. Our aim is to listen to these absences and discuss how they influence and possibly reshape the practices of listening, as well as notions of the child and childhood.